Augmentation of GNSS autonomous positioning using a ground based ZigBee phase shift distance measurement - Janowski, Artur; Rapinski, Jacek (International Conference “Environmental Engineering”, 2017)
The article presents the impact of GNSS positioning system augmentation using a ZigBee device. Ground based augmentation is based on the distance measurement between two ZigBee devices – one embedded into the rover and one acting as an anchor. The paper describes the device that was used in the experiment along with experiment results. Experiment results shows the significant impact of an additional distance measurement on the positioning results, especially in the case when there is a small number of satellites in view.